Epilepsy in China: major progress in the past two decades. Issue 4 (April 2021) - Ding, Ding; Zhou, Dong; Sander, Josemir W; Wang, Wenzhi; Li, Shichuo; Hong, Zhen
Summary: China has approximately 10 million people with epilepsy. There is a vast epilepsy treatment gap in China, mainly driven by deficiencies in health-care delivery and social discrimination resulting from cultural beliefs about epilepsy. WHO's Global Campaign Against Epilepsy project in China showed that it was possible to treat epilepsy in primary care settings, which was a notable milestone. The China Association Against Epilepsy has been a necessary force to stimulate interest in epilepsy care and research by the medical and scientific community. Nearly 20 different anti-seizure medications are now available in China. Non-pharmacological options are also available, but there are still unmet needs for epilepsy management. The Chinese epilepsy research portfolio is varied, but the areas in which there are the most concentrated focus and expertise are epidemiology and clinical research. The challenges for further improvement in delivering care for people with epilepsy in China are primarily related to public health and reducing inequalities within this vast country.